2015
DOI: 10.1126/science.aaa1738
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA control of protein expression noise

Abstract: MicroRNAs (miRNAs) repress the expression of many genes in metazoans by accelerating messenger RNA degradation and inhibiting translation, thereby reducing the level of protein. However, miRNAs only slightly reduce the mean expression of most targeted proteins, leading to speculation about their role in the variability, or noise, of protein expression. We used mathematical modeling and single-cell reporter assays to show that miRNAs, in conjunction with increased transcription, decrease protein expression nois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
387
4
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 370 publications
(418 citation statements)
references
References 40 publications
25
387
4
2
Order By: Relevance
“…Although earlier studies identified the stronger and more recognizable phenotypes of a few miRNAs (e.g., let-7), the majority of miRNAs exert subtle effects. It has been suggested that this is because miRNAs function to dampen noise arising from the stochastic nature of gene expression or raise the threshold required to elicit a response (Hornstein and Shomron 2006;Ebert and Sharp 2012;Ameres and Zamore 2013;Schmiedel et al 2015). This may explain why it has been so difficult to assign a clear-cut function to many miRNAs and why inactivation of a particular miRNA rarely gives rise to severe defects.…”
Section: Introductionmentioning
confidence: 99%
“…Although earlier studies identified the stronger and more recognizable phenotypes of a few miRNAs (e.g., let-7), the majority of miRNAs exert subtle effects. It has been suggested that this is because miRNAs function to dampen noise arising from the stochastic nature of gene expression or raise the threshold required to elicit a response (Hornstein and Shomron 2006;Ebert and Sharp 2012;Ameres and Zamore 2013;Schmiedel et al 2015). This may explain why it has been so difficult to assign a clear-cut function to many miRNAs and why inactivation of a particular miRNA rarely gives rise to severe defects.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNA (miRNA), 3 small non-coding RNA sequences (ϳ22 nucleotides), have been heralded as regulators of gene expression that control postranscriptional mRNA stability or translation (4,5). miRNAs tune out transcriptional noise, allowing tighter control over protein expression of critical proteins defining a cell (6). Much like miRNA, glycosylation has the ability to exert global regulatory effects within the cell and its surroundings, and dysregulation can lead to biological disorders (7).…”
mentioning
confidence: 99%
“…The case F≃ 0 corresponds to the experimental situation reported in Ref. [26]. In this limit, I opt = 2.91 and I T F opt = 1.74.…”
Section: Summary and Discussionmentioning
confidence: 61%
“…The modelling of the post-transcriptional regulation is based on the mathematical models proposed in [25,26]. The models derive their strength from the fact that the theoretical results closely match the experimental observations in single cell measurements.…”
Section: Dynamics Of Two-gene and Fourgene Motifsmentioning
confidence: 99%